Os desafios na docência: contribuições para a formação de uma professora da educação básica - MERCÊS, Ana Maria Silva das (2024)
This memorial has the objective summarizes my challenges in the teaching, highlighting my schooling since childhood, until graduation, through the National Plan for Teacher Training (PARFOR), my teaching practice. For this reason, I sought authors who had talks within the experiences, among them: Brandão (2014). Ortiz (2005), Freire (2005), Durkheim (1982), among others. This memorial has as objective resume my memories and souvenirs, highlighting my schooling since childhood, until graduation, through the National Plan for Teacher Training (PARFOR), my teaching practice. For this reason, I sought authors who had talks within the experiences, among them: Brandão (2014). Ortiz (2005), Freire (2005), Durkheim (1982), among others. I resumed my memories from childhood, to realize the differences and through addition to believe in better days; my school life was always full of challenges, but they allowed me to get up here. My professional experiences, gave me the basis, until my encounter with what really wanted: the magisterium, which conquered with difficulty and overruns that were part of my training in those four years of undergraduate studies, and these experiences changed my life and perfected my pedagogical practice.